Development of intelligent monitoring and control system for mine ventilation safety - YANG Zhanqi; HAO Tianxuan (Gong-kuang zidonghua, 2017)
In order to realize automatic adjustment and control of air volume during mine normal production or disaster relief, an intelligent monitoring and control system for mine ventilation safety was developed. Structure, hardware configuration and software development of the system were introduced. The system can real-timely monitor and display ventilation safety parameters, such as wind speed, gas concentration, temperature, air pressure and air volume, which can provide basis for disaster pre-warning and control. The system can also automatically adjust opening and closing state and opening degree of air door when air volume is insufficient or rich, which can meet need of air supply for ventilation location and disaster relief.